Exercise-induced hypoxemia: Fact or fallacy? - Scroop, G. C.; Shipp, N. J. (Medicine & Science in Sports & Exercise, 2010)
Whereas the prevalence of exercise-induced hypoxemia (EIH) in endurance athletes is commonly reported as ~50%, most previous studies have not corrected PaO2 for exercise-induced hyperthermia. Furthermore, although a detrimental effect on aerobic performance has been assumed, no study has measured arterial oxygen content (CaO2) in this context.